EFEKTIFITAS PENGGUNAAN MEDIA PEMBELAJARAN E-LEARNING PADA MATA KULIAH QOWAIDULLUGHOH DI PRODI PAI FAI UHAMKA - Fitriliza Fitriliza (Universitas Muhammadiyah Prof Dr Hamka, 2019)
E-learning based learning media is technology based learning where learning material is presented in the form of audio visual such as video. This type of research is an experimental study to determine the effectiveness of learning media that is treated. The study population was all semester II PAI UHAMKA students in South Jakarta. The sample used in this study was taken randomly, namely the PAI classes A, B and C. The data collected included primary data. The results of this study were obtained from primary data. Primary data were obtained from pre-test and post-test results of students. There is an increase in the pre-test and post-test results in the experimental class and a decrease in the pre-test and post-test results in the control class. The average results obtained from the experimental class from 59.36 to 71.76 and in the control class from 72.82 to 70.64. The difference in mean results shows an increase in pre-test and post-test results and it can be concluded that the e-learning-based learning media is effectively used in learning.